RELATIONSHIP BETWEEN MOTHER’S PARTICIPATION IN SUPPORT GROUPS WITH EXCLUSIVE BREASTFEEDING PRACTICE IN PUSKESMAS UMBUL HARJO I YOGYAKARTA, INDONESIA - Nur Laela; Siti Naili Ilmiyani; Etni Dwi Astuti; Warsiti Warsiti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: By the Indonesian Demographic and Health Survey (IDHS) in 2012, infant mortality rate in Indonesia is still quite high at 32 deaths per 1,000 live births. The majority of infant deaths occur in the neonatal period. The main capital in achieving quality health starts since the beginning with breastfeeding without any additional food in this case of exclusive breastfeeding. Many mothers do not provide exclusive breastfeed due to social factors (maternal employment, social, cultural, supportfamily). Aims: This paper explains the relationship between the rate of participation in maternal supporting group with the success of exclusive breastfeeding program in Community Health Centers Umbulharjo I Yogyakarta in 2014. Methods: This study employed correlation analytical survey with cross sectional approach. The samples were 30 mothers who having a baby age 6 to 12 months, and participated in a maternal supporting group. Results: Of the 30 respondents, 26 (86.7%) of respondents successfully breastfeed exlusive. Of which 23 respondents (76.7%) with a participation rate of mothers in support groups with good category, 22 (73.3%) were successful exclusive breastfeeding and 1 (3.3%) of respondents who did not give exclusive breastfeeding, in the medium category 3 respondents (10.0%), 2 respondents (6,7%) were successful exclusive breastfeeding, and 1 (3.3%) of respondents who did not give exclusive breastfeeding, and low category 4 respondents (%13.3), 2 respondents (6,7%) were successful exclusive breastfeeding and 2 (6.7%) of respondents who did not give exclusive breastfeeding. The participation rate of mothers in maternal supporting group affects the success of exclusive breastfeeding with the P value = 0.026. Conclusion: There was a significant relationship between the rate of participation of mothers in maternal supporting group success exclusive breastfeeding mothers. The social relations become very important to increase the exclusive breastfeeding through mother support groups.